2012
DOI: 10.1039/c2mb25228g
|View full text |Cite
|
Sign up to set email alerts
|

The changes of microRNA expression profiles and tyrosinase related proteins in MITF knocked down melanocytes

Abstract: Microphthalmia-associated transcription factor (MITF) is a master regulator in melanocyte proliferation, development, survival and melanoma formation. In melanocyte dysfunction disease, it is observed that the expressions of MITF, tyrosinase (TYR), tyrosinase related protein 1 (TYRP1) and tyrosinase related protein 2 (TYRP2)/dopachrome tautomerase (DCT) are changed, the consequence of which remains unclear. In this study, we focused on the change of microRNA (miRNA) profiles and Tyrosinase Related Proteins (TR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 42 publications
2
15
0
Order By: Relevance
“…Moreover, TYRP1 gene promoter contains a motif, termed M-box, that can bind to the microphthalmia-associated transcription factor (MITF) (Ghanem and Fabrice, 2011). However, MITF is a master regulator in melanocyte proliferation, development, survival and melanoma formation (Wang et al, 2012). Additionally, studies have suggested that TYRP1 may help to stabilize tyrosinase (Kobayashi et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, TYRP1 gene promoter contains a motif, termed M-box, that can bind to the microphthalmia-associated transcription factor (MITF) (Ghanem and Fabrice, 2011). However, MITF is a master regulator in melanocyte proliferation, development, survival and melanoma formation (Wang et al, 2012). Additionally, studies have suggested that TYRP1 may help to stabilize tyrosinase (Kobayashi et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are small non-coding RNAs that have been plays an important role in embryogenesis, organ development, cell proliferation, metabolism, embryogenesis, behaviour and other biological processes [14][15][16][17][18][19]. Recently, miRNAs were reported to play important roles in regulating hair follicle morphogenesis and the proliferation, differentiation and apoptosis of hair follicle stem cells in mice, rats, goats and sheep [20][21][22]. Notably, miR-214 inhibits hair follicle growth and development by modulating the expression of regulatory factors in Wnt signalling pathway, such as β-catenin and lymphoid enhancer-binding factor 1 (Lef-1) [23].…”
mentioning
confidence: 99%
“…MicroRNAs (miRNAs) are small (~22 nucleotides long) non-coding RNAs that have been proposed to play important roles in diverse biological processes [14], such as organ development, cell proliferation, tumourigenesis, lipid metabolism, behaviour and embryogenesis [15][16][17][18][19]. Recently, miRNAs were reported to play important roles in regulating hair follicle morphogenesis and the proliferation, differentiation and apoptosis of hair follicle stem cells in mice, rats, goats and sheep [20][21][22]. Notably, miR-214 inhibits hair follicle growth and development by modulating the expression of regulatory factors in Wnt signalling pathway, such as β-catenin and lymphoid enhancer-binding factor 1 (Lef-1) [23].…”
mentioning
confidence: 99%